Transapical Approach for Mitral Valve Repair during Insertion of a Left Ventricular Assist Device. (26th June 2013) - Russo, Mark J.; Merlo, Aurelie; Johnson, Elizabeth M.; Akhter, Shahab; McCarney, Sean; Steiman, Jennifer; Anderson, Allen; Jeevanandam, Valluvan
Abstract : Background . Severe mitral regurgitation (MR) is common in patients who are undergoing insertion of a left ventricular assist device (LVAD). This study analyzes the outcomes of a transapical approach for edge-to-edge repair of the mitral valve during insertion of a left ventricular assist device in 19 patients with MR. Methods . This retrospective study includes 19 patients who were implanted between March 21, 2011, and August 31, 2011, at the University of Chicago. Clinical data include preoperative ejection fraction, post- and preoperative pulmonary arterial pressures, cardiopulmonary bypass time, post- and preoperative mitral regurgitation severity, endotracheal CO2, and LVAD pulse index. Results . All of the 19 patients had a reduction in mitral regurgitation. Fourteen of the 19 patients had at least a three-point reduction in MR severity. The average postoperative pulmonary arterial pressure (PAP) decreased after the surgical procedure from 44/22 ± 14/5 mmHg to 57/28 ± 9/5 mmHg. Average CPB time was 128 ± 27 minutes. Average length-of-stay (LOS) was 21 ± 10 days. Conclusions . Concomitant MV repair using a transapical approach is advantageous for this small cohort of patients. The surgical procedure is less complex and has a shorter CPB time and LOS, and all of the patients demonstrated significant improvement in postoperative MR and moderate improvement in PAP.